2002
DOI: 10.1116/1.1430249
|View full text |Cite
|
Sign up to set email alerts
|

Density changes upon crystallization of Ge2Sb2.04Te4.74 films

Abstract: Articles you may be interested inEffects of germanium and nitrogen incorporation on crystallization of N-doped Ge2+xSb2Te5 (x=0,1) thin films for phase-change memory J. Appl. Phys. 113, 044514 (2013); 10.1063/1.4789388Crystallization of sputtered-deposited and ion implanted amorphous Ge 2 Sb 2 Te 5 thin films

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

21
177
4

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 350 publications
(205 citation statements)
references
References 7 publications
21
177
4
Order By: Relevance
“…Using this procedure, we will be able to take the volume changes in amorphization as a fingerprint in which to compare our multiple configurations and potential pathways against experimental results. 10,36,62 First, we compared the a-GST structures generated using cubic and hexagonal unit cells from high temperature MD simulations. The pair correlation functions for all pairs of atoms ͑Ge-Te, Ge-Sb, Sb-Te, Ge-Ge, Sb-Sb, and Te-Te͒ were obtained by averaging the pair correlation functions over about ten structures for both unit cells.…”
Section: Amorphous Gst Phasementioning
confidence: 99%
See 2 more Smart Citations
“…Using this procedure, we will be able to take the volume changes in amorphization as a fingerprint in which to compare our multiple configurations and potential pathways against experimental results. 10,36,62 First, we compared the a-GST structures generated using cubic and hexagonal unit cells from high temperature MD simulations. The pair correlation functions for all pairs of atoms ͑Ge-Te, Ge-Sb, Sb-Te, Ge-Ge, Sb-Sb, and Te-Te͒ were obtained by averaging the pair correlation functions over about ten structures for both unit cells.…”
Section: Amorphous Gst Phasementioning
confidence: 99%
“…61 Ge-Ge and Ge-Sb bonds are found in those motifs, which is assumed to be due to disorder effects, since they are not present in the crystalline phases. Furthermore, a-GST shows volume expansion of 6%-7% compared with the m-GST phase, 10,36,62 and it has a higher energy ͑28-40 meV/at.͒ with respect to m-GST. 63 Based on EXAFS studies and Ge coordination change, Kolobov et al 54 suggested that the m-GST to a-GST transition is related to an umbrella flip of Ge atoms from octahedral to tetrahedral sites without the rupture of strong covalent bonds.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The thermal properties of GST family were measured and studied in details, and the studies showed that there were common characteristics for different members in the GST family due to the distorted NaCl-type rock structures [21,22]. Accordingly, the thermal model of memory devices based on the GST family was established [6,23].…”
Section: Introductionmentioning
confidence: 99%
“…With the development of the phase-change memory, various materials were examined, and the materials of the best performances in terms of speed and stability were found to be GeSbTe (abbreviated as GST) family, such as Ge 2 Sb 2 Te 5 and Ge 1 Sb 4 Te 7 [4,9,16,17,[21][22][23], and AgInSbTe (abbreviated as AIST) family, such as Ag 3.4 [2,3,7,[11][12][13][14][15][24][25][26][27][28]. The thermal properties of GST family were measured and studied in details, and the studies showed that there were common characteristics for different members in the GST family due to the distorted NaCl-type rock structures [21,22].…”
Section: Introductionmentioning
confidence: 99%